Persepsi Masyarakat Terhadap Objek Wisata Kolam Ikan Teras Alam Ulin Di Kelurahan Sempaja Utara Kecamatan Samarinda Utara - Rina Aprila; Fitriyana Fitriyana; Juliani Juliani (Ekonomi Keuangan Syariah dan Akuntansi Pajak, 2024)
According to the Law of the Republic of Indonesia Number 10 of 2009 concerning Tourism, tourism is defined as a variety of tourist activities supported by various facilities and services provided by the community, entrepreneurs, and local governments. This study aims to determine the public perception of the Ulin Nature Terrace tourist attraction in North Sempaja Village, North Samarinda District. The data required are primary data and secondary data according to the research objectives. Based on the results of the study, it is known that people's perceptions of tourist attractions use sapta charm indicators, namely security, order, cleanliness, coolness, beauty, friendliness, and memories. The highest indicator is beauty (1,273) and the lowest is hospitality (1,192). Overall, people's perceptions are classified as good because the value of 8,519 is in the interval range 7,140 - 8,819, meaning that the community views the existence of these attractions as positive and beneficial, because these attractions not only offer tourist attractions in the form of fish therapy, but other interesting panoramas.